Principlism and citizen science: the possibilities and limitations of principlism for guiding responsible citizen science conduct. (October 2022) - Baard, Patrik; Sandin, Per
Citizen science (CS) has been presented as a novel form of research relevant for social concerns and global challenges. CS transforms the roles of participants to being actively involved at various stages of research processes, CS projects are dynamic, and pluralism arises when many non-professional researchers take an active involvement in research. Some argue that these elements all make existing research ethical principles and regulations ill-suited for guiding responsible CS conduct. However, while many have sought to highlight such challenges from CS, few have discussed principles per se providing the foundation for regulations. In this article we will investigate the possibilities of midlevel principlism in guiding responsible CS conduct. Principlism has the potential of accommodating many of the concerns taken to reduce the relevance of existing principles.